Notes on Indian Grasses-II. the Identity and Distribution of Certain Species - Jain, S. K. (Indian Forester, 1966)
The identity and distribution in India of ten grasses, namely, Bothriochloa caucasica (Trin.) Hubb., Capillipedium filiculme (Hook. F.) Stapf, Dimeria connivens Hack., Sorghum controversum (Steud.) Snowden, Digitaria tomentosa (Koenig) Henr.,Panicum atrosanguineum Hochst. Ex A. Rich., Urochloa panicoides P. Beauv. Var. velutina (Henr.) Bor, Polypogon fugax Nees ex Steud., Dactyloctenium aristatum Link and Hordeum bogdanii Wilensky are discussed; the last named grass is reported from India for the first time.